@rte.ma: elaboração de Meio de Ensino e Aprendizagem/MEA para Educação Básica do estado do Maranhão a partir de produções das artes visuais maranhense do século XXI. - FARIAS, Monica Rodrigues de (2018)
This research comes from the verification of the absence of teaching materials geared to the issues related to the local visual arts, required for use by art teachers of the Maranhão state basic education. Faced with this problem raised in field research activities, documentary and bibliographic over ten maranhenses visual artists of the XXI century and their works, rose the materials necessary sources for creation of Teaching and Learning Media - to be designated by the acronym " MEA "this search: visual boards (each with two reproductions of works of each artist front and back); a documentary (made by the issue of copyright short films based on interviews with the artists surveyed stored on DVD device; an educational notebook (with information about the artist and his works and tips / visual reading proposals for educational support teacher / mediator). Information and Communication Technologies (ICTs) are the support tools at various times from the initial stage of choosing the names of the artists to be searched by applying the Delphi method, and also data collection activities and field research. The methodology used was the action research, because of the need for collaborative action between teacher / researcher and researchers / students, leading a research group entitled PesquisAção. The Art of States that underpin this work follow the following areas: Teaching Visual Arts / Visual Arts Maranhense / MEA / ICT. The MEAs are presented as a practical result in prototypes, since they were perfected in works subsequent to the conclusion of this research.